Fodder, Grain Yield, Nitrogen uptake and Crude Protein of Forage Maize as Influenced by Different Nitrogen Management Practices - Reddy, D. Madhusudhan; Bhanumurthy, V. B. (International Journal of Bio-resource and Stress Management, 2010)
A field study was conducted during three consecutive rabi seasons at Dairy Experimental Station, Livestock Research Institute, Rajendranagar to evaluate forage maize grown for green fodder, dry fodder and grain (GDG maize) with three nitrogen levels (120, 180 and 240 kg N ha-1) and four times of nitrogen application, i.e. 0, 30 days after sowing (DAS); 0, 30, 70 DAS; 0, 30, 95 DAS and 0, 30, 70, 95 DAS. Zero denotes application of the nutrient at the time of sowing. The above combination of twelve treatments was compared with three checks, viz. normal grain maize (60x25 cm2 spacing), double density grain maize (30x25 cm2 spacing) and maize sown at 30x25 cm2 for green fodder at recommended dose of nitrogen (120 kg N ha-1) following a randomized block design (RBD). A uniform dose of 60 kg P2O5 ha-1 and 40 kg K2O ha-1 was applied as basal dose. It was found that GDG maize grown by applying 240 kg N ha-1 in three splits (0, 30 and 70 DAS) gave significantly higher grain ((3.9 t ha-1) and stover (8.3 t ha-1) yield, N uptake (273.4 kg ha-1), crude protein yield (1695 kg ha-1) and net returns (INR 24,509 ha-1). However, it was comparable with that of normal grain maize in terms of grain and stover yield and was comparable with GDG maize at 240 kg N ha-1 in two splits (0, 30 DAS) in respect of N uptake and crude protein yield. Total dry matter production was significantly higher with double density grain maize. The study revealed that GDG maize system can be practiced for simultaneous harvest of green fodder and dry fodder economically.